Professionalization of Teaching in Nigeria: Strategies, Prospects and Challenges - Oluremi Dorcas Fareo (Intelektual Pustaka Media Utama, 2015)
The teaching profession in Nigeria has gone through many stages and even today there are disagreements as to whether it should be called a profession; and this has been an issue of concern among educators, teachers, administrators, organizations and the public at large. This paper thus looked into the issue of professionalizing teaching for the development of the education sector in the country. The concepts of teaching and profession were viewed; traits of professionalism; the teaching profession in Nigeria; strategies, prospects and challenges facing teaching profession were identified; The study recommended that the government should look into the problem of general dissatisfaction with the teaching profession, such as poor teacher education programme; poor salaries and allowances; poor public image of the profession; and the desire of most teachers to enter another type of work with attractive remunerations,